2022
DOI: 10.1111/1755-0998.13625
|View full text |Cite
|
Sign up to set email alerts
|

For all audiences: Incorporating immature stages into standardised spider inventories has a major impact on the assessment of biodiversity patterns

Abstract: Although arthropods are the largest component of animal diversity, they are traditionally underrepresented in biological inventories and monitoring programmes. However, no biodiversity assessment can be considered informative without including them.Arthropod immature stages are often discarded during sorting, despite frequently representing more than half of the collected individuals. To date, little effort has been devoted to characterising the impact of discarding nonadult specimens on our diversity estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 99 publications
(102 reference statements)
0
12
0
Order By: Relevance
“…Such potential seems to have been appreciated most acutely by arachnologists. When explicitly incorporating immatures, Domènech et al (2022) found that not only were juvenile spiders the most abundant individuals across several sampling techniques and areas, they contributed nearly 30% to the final species total. Similar results were found in spider surveys by Ding et al (2023) and Blagoev et al (2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such potential seems to have been appreciated most acutely by arachnologists. When explicitly incorporating immatures, Domènech et al (2022) found that not only were juvenile spiders the most abundant individuals across several sampling techniques and areas, they contributed nearly 30% to the final species total. Similar results were found in spider surveys by Ding et al (2023) and Blagoev et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…The emphasis in systematics on one semaphoront has limited, whether by design or by necessity, biodiversity inventory efforts to focusing preferentially on the most identifiable specimens, ignoring or regarding others as uninformative, or as an unavoidable nuisance (Domènech et al, 2022). For instance, in insects, the most widely publicized data associated with reports of overall declines have been entirely based on flying (therefore adult) insects collected by light and Malaise traps (Hallmann et al, 2017;Lister & Garcia, 2018;Mata et al, 2021), and many more general inventory attempts focus mainly on flight-trapped insects, mostly excluding other semaphoronts (Chimeno et al, 2023;Kaczmarek et al, 2022;Li et al, 2023;Montgomery et al, 2021;Srivathsan et al, 2023;Steinke et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spider juvenile identification is very important in spider studies ( Domènech et al 2022 ). Most juveniles, with the exception of some exotic Erigoninae , were also included in the data presented in this paper, since the low diversity of spiders in the Azores allows a relatively precise species-level identification of this life-stage.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…DNA barcoding relies on the analysis of a specific small genomic region (for metazoans usually a fragment of the mitochondrial cytochrome c oxidase subunit 1) for molecular species identification. This is particularly useful in spiders for identifying juvenile specimens, in which diagnostic morphological characters are still not visible, for matching males and females of the same species and as an aid to traditional 2 taxonomy when dealing with cryptic or problematic taxa (Hebert et al 2003, Domènech et al 2022b. In contrast to other European countries (see, e.g., Astrin et al 2016, Domenec et al 2022a, in Italy no projects are currently focusing on creating a DNA barcode library of Italian spider species.…”
Section: Introductionmentioning
confidence: 99%